Tenosynovial giant cell tumor of subtalar joint: A case report with review of literature - Daya Krishna; Vipan Kumar; Subhash Chand; Vikesh Bhatt; Anu Yarky (Journal of Orthopedics, Traumatology and Rehabilitation, 2017)
Tenosynovial giant cell tumor (TSGCT) are benign neoplasm affecting synovial lining of joints, tendon, and bursae. These tumor have been broadly divided into localized and diffuse type. Localized include TSGCT of tendon sheath and localized pigmented villonodular synovitis (PVNS) located mainly in hand whereas diffuse encompass conventional PVNS and diffuse-type GCT involving one or more joints. In this article, here, we present a case of TSGCT in subtalar joint which has been never reported till date along with review of literature, dilemma in diagnosis, differential diagnosis, and management of this tumor.